PENGARUH GENDER TERHADAP MOTIVASI BERPRESTASI SISWA SMP KELAS VIII DALAM PEMBELAJARAN BERDASARKAN MASALAH - Iman Santoso, Fransiskus Gatot (Widya Warta, 2015)
The objective of this study is to determine the influence of gender on achievement motivation of the eighth year students of junior high school in problem based learning. The scope of  the research includes (1) gender, that is, the sex of the students as male and female and (2) the students' achievement motivation in mathematics, namely achievement motivation in mathematics of the eighth year students of state junior high schools of Madiun municipality 2013/2014. The aspects of achievement motivation in this case comprise (a)having desires to try themselves, (b) being fond of challenging tasks, (c) being eager to move forward; (d) being resilient to face obstacles, and (e) being future oriented. The subject of this study was the eighth year students of junior high school  of 2013/2014. This  research is descriptive quantitative in nature with research design using secondary data. The data were collected applying documentation technique. It was used to determine the gender of students and their achievement motivation in mathematics. The data analysis employed statistical hypothesis testing of student-t test. The results indicated that there was no difference of the students’ average achievement motivation in mathematics based on gender in problem based learning, which means there was no influence of gender on achievement motivation of the eighth year students of junior high school in problem based learning.